AMERICAN VALUES MANIFESTATION PORTRAYED BY ATOM IN REAL STEEL THE MOVIE - DARMIANTI, SELVY (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: American Values, Popular Culture, Real Steel, Robot CharacterMovie is one of popular cultures that reflect the condition of society. It could be in the forms of phenomena, idea, or culture. This condition also happens in American’s movies, one of them is Real Steel. Unlike other movies representing American values depicted by human character, this movie is depicted by the nonhuman character, i.e. robot.Sociological approach is used in this study since Real Steel the movie describes a lot of American social phenomena. Scene and subtitle will be categorized and analyzed using relevant American values theory.  The result reveals that four out of six American values as proposed by Datesman, et al. are found in this study, they are equality of opportunity, and competition, material wealth and hard-work. Whereas two of them, individual freedom and self-reliance are not found. Furthermore, from Atom’s journey it shows that Americans respect the equality of opportunity; assume that competition is an obligation, benchmark wealth as a status and respecthardworking in the journey of success.In the future, boxing, as one of roughest sports, are performed by robots, because robots are more resistant to take blows rather than humans. So, the next researchers can use humanism theory to analyzed Real Steel the movie.